The model of swarm robots search with local sense based on artificial physics optimisation. (1st January 2013) - Xie, Liping; Yang, Gangjun; Zeng, Jianchao
Swarm robots search is an effective method for rescue operation and victim search in some disaster. Due to robot's limited sensing capability in practical applications, time-varying sense domain is introduced to denote robot's dynamic neighbourhood structure. Artificial physics optimisation (APO) algorithm is used to construct the model of swarm robots system. Then, the model of swarm robotic search for target with local sense based on APO is proposed, which include robot's mass function designing, force definition and the cooperative control strategy description. Simulation results under an ideal environment show that APO algorithm is feasible and effective when applied to swarm robotic search for target with local sense.